The Impact of Macroeconomic Factors on the Sukuk Market Development with an Emphasis on the Role of Financial Risk in Selected Islamic Countries - Hadis Dalvandi; Habib Ansari Samani; Ali Lamea (تحقیقات مالی اسلامی (پیوسته))
In recent years, the sukuk market has grown significantly. The sukuk market, as a financial instrument, plays a positive and important role in the country's economic growth by stimulating capital accumulation and promoting the efficient allocation of resources. Macroeconomic factors are one of the most important factors affecting on the sukuk market development. The purpose of this research is to investigate the impact of macroeconomic factors on the sukuk market development with an emphasis on the role of financial risk in 11 selected Islamic countries for the period of 2013-2021 and using the panel ordinary least squares method. The results show that in the studied countries, the impact of financial risk, interest rate fluctuations and institutional quality on the sukuk market development is negative and significant, while, the stock market development, inflation and exports have a positive and significant impact on the sukuk market development. Moreover, the results did not show a significant impact of the banking sector development on the sukuk market development. An increase in financial risk causes an increase in uncertainty and instability and a decrease in the confidence of investors, and as a result, investors prefer to make less risky investments. Therefore, financial risk has a negative and significant impact on the sukuk market development. The findings of this study are significant for policy makers, governments and regulators in formulating policies to improve the current situation of the sukuk market.